2008
DOI: 10.1016/j.nuclcard.2007.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear medicine imaging of takotsubo cardiomyopathy: Typical form and midventricular ballooning syndrome

Abstract: Transient left ventricular (LV) apical ballooning syndrome, also known as takotsubo cardiomyopathy (TTC), was first described in the early 1990s in Japan. 1 TTC symptoms and electrocardiographic findings are close to those of acute myocardial infarction. 2 Cardiac enzyme levels, such as creatinine phosphokinase and troponin I, are slightly increased. During the acute phase, 2-dimensional transthoracic echocardiography (TTE) demonstrates akinesia or dyskinesia of the apical and midventricular segments associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…In keeping with other published studies however, myocardial perfusion was not completely absent even on the stress study [6]. In fact, some reports have noted that myocardial perfusion may be completely normal despite significant wall motion abnor- malities and the presence of symptoms [7,8]. Although the perfusion abnormality in the apex can be partially explained by a partial volume effect involving the non-thickening apical segments [9,10], many studies have demonstrated that microvascular dysfunction may be responsible for a true perfusion defect [6,11,12].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In keeping with other published studies however, myocardial perfusion was not completely absent even on the stress study [6]. In fact, some reports have noted that myocardial perfusion may be completely normal despite significant wall motion abnor- malities and the presence of symptoms [7,8]. Although the perfusion abnormality in the apex can be partially explained by a partial volume effect involving the non-thickening apical segments [9,10], many studies have demonstrated that microvascular dysfunction may be responsible for a true perfusion defect [6,11,12].…”
Section: Discussionsupporting
confidence: 89%
“…Reduction in fatty acid metabolism occurs under conditions of ischemia and has been documented through SPECT imaging with I-123 BMIPP [6, 12]. On PET imaging, reduced perfusion with N-13 ammonia [13] and decreased metabolism with F-18 FDG imaging has also been described [7,13]. The radio-iodinated analog for norepinephrine I-123 MIBG has also been used to demonstrate a suppression of myocardial sympathetic nerve function in response to myocardial ischemia in TC.…”
Section: Discussionmentioning
confidence: 99%
“…In the acute and subacute phases of stress-induced cardiomyopathy, the affected hypocontractile ventricular segment shows defects of MIBG and FDG uptake despite normal to slightly reduced perfusion. Subsequent rapid normalization of myocardial perfusion and delayed recovery of both LV glucose metabolism and sympathetic innervation are also observed [25,26].…”
Section: Nuclear Imagingmentioning
confidence: 93%
“…Single-photon emission computed tomography can assess neurogenic myocardial stunning, a consequence of defects in myocardial perfusion and sympathetic innervation, using 201 Thallium or 99m Technetium-labelled radiopharmaceuticals and 123 I-metalodobenzylguanidine (I-123 MIBG). Likewise, 18F-fluorodeoxyglucose (FDG) positron emission tomography can be used to detect myocardial glucose metabolism [25,26]. In the acute and subacute phases of stress-induced cardiomyopathy, the affected hypocontractile ventricular segment shows defects of MIBG and FDG uptake despite normal to slightly reduced perfusion.…”
Section: Nuclear Imagingmentioning
confidence: 99%
“…The mid-ventricular type: accounts for ~40% [10] is characterized by transient LV midsegment akinesis but preservation of LV apical segment [17]. The localized type: is characterized by any other segmental LV dysfunction with clinical characteristics similar to takotsubo-like LV dysfunction.…”
Section: Typesmentioning
confidence: 99%